Pengaruh Tingkat Kesehatan Bank Dengan Metode Risk Based Bank Rating ( RBBR) Terhadap Kinerja Keuangan ( Studi Kasus Pada Bank Umum Yang Terdaftar Di BEI Periode Tahun 2017-2019) - Mellyn Arinda Veranita; Afi Rahmat Slamet; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to know the impact of the bank's health level with the risk based bank rating ( RBBR) on financial performance at the public bank listed on the IDX for the period 2017-2019. The data source in this study used the company's annual report which was downloaded through the website of the Indonesian stock exchange and the company. Based on the test results, it can be concluded that non-performing loan (NPL) and net interest margin (NIM) have a significant effect on financial performance, while loan to deposit ratio (LDR), good corporate governance (GCG) and capital adequacy ratio (CAR) have no significant effect on financial performance. Keywords: Bank Health, Risk Based Bank Rating, Financial Performance